2007
DOI: 10.1017/s000711450782513x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a comprehensive fruit- and vegetable-promoting school-based intervention in three European countries: the Pro Children Study

Abstract: The objective of the present study was to evaluate the effects of the Pro Children intervention on schoolchildren's fruit and vegetable (FV) intake after 1 and 2 years of follow-up. The intervention combined a FV curriculum with efforts to improve FV availability at schools and at home. Effects were examined in a group-randomised trial among 1472 10 -11-year-old children from sixty-two schools in Norway, the Netherlands and Spain. FV intake was assessed by means of validated self-administered questionnaires co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
113
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 35 publications
6
113
1
7
Order By: Relevance
“…This is in accordance with the findings of other intervention studies, such as the European Pro Children Study and the Norwegian Fruit and Vegetables Makes the Marks (FVMM) project, which observed somewhat higher effect sizes (20,21) at longer-term follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with the findings of other intervention studies, such as the European Pro Children Study and the Norwegian Fruit and Vegetables Makes the Marks (FVMM) project, which observed somewhat higher effect sizes (20,21) at longer-term follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…The components designed and used in this programme are similar to those used in other multi-component interventions which have been shown to be effective (5,10,14,17,19,22) . However, implementation rate is a vital component in the success of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…To tackle this issue, the Project Tomato intervention incorporated fun activities for parents and children to do together at home, because parents play a direct role in their child's eating behaviours and attitudes towards food (4,5) . Several systematic reviews have summarised existing research on school interventions to increase children's fruit and vegetable intake (6)(7)(8) and these reviews suggest multi-component interventions are the most successful in terms of improving fruit and vegetable consumption (9)(10)(11)(12)(13)(14)(15)(16)(17) , supporting the design methodology used to create the Project Tomato intervention. Some of the successful studies that have previously used multi-component interventions included the following elements in their interventions:…”
mentioning
confidence: 99%
“…Therefore, several school-based or family-based initiatives have been implemented in order to promote F&V intake among schoolchildren (24)(25)(26)(27)(28) . These programmes had a positive effect on actual intake levels among this target group in the countries where they were implemented.…”
mentioning
confidence: 99%